Teaching Grammar In Context: A Contextual Approach To Language Learning (Journal of Pedagogical Inventions and Practices, 2025)
Grammar instruction has traditionally followed a prescriptive and decontextualized model, often disconnected from real language use. Recent pedagogical research, however, highlights the advantages of teaching grammar in context, promoting more meaningful learning and communicative competence. This study investigates the effectiveness of contextual grammar teaching among intermediate ESL learners. The research uses a quasi-experimental design with pre- and post-tests, comparing two groups—one receiving traditional grammar instruction and the other taught using contextualized tasks. Results indicate that learners exposed to contextual grammar instruction demonstrate better retention and application of grammatical structures. The study underscores the importance of integrating grammar teaching with authentic language use in communicative settings.